Field evaluation of the prophylactic effect of an isometamidium sustained-release device against trypanosomiasis in cattle - Diarra, B.; Diall, O.; Geerts, S.; Kageruka, P.; Lemmouchi, Y.; Schacht, E.; Eisler, M.C.; Holmes, P. (1998)
In order to compare the prophylactic effect provided by a poly(D,L-lactide) sustained-release device (SRD) containing isometamidium (ISMM; Trypamidium) with that provided by the classical im injection of the drug, a field trial was carried out at the Madina Diassa Ranch in Mali, beginning in November 1995. One- to 3-year-old N'Dama cattle were randomly divided into 3 groups. The first group (n = 42) was treated with ISMM at a dose of 1 mg/kg bwt, the 2nd group (n = 44) received the same dose of the drug via an SRD, which was subcutaneously implanted in the shoulder region, and the 3rd group (n = 36) was kept as untreated controls. All animals were treated with diminazene aceturate (7 mg/kg of bwt) 2 weeks before the start of the experiment and were tested monthly by the buffy coat technique for a period of 8 months. Glossina morsitans submorsitans was the most important tsetse species, with apparent densities (number of catches/trap/day) varying between 11.9 and 38.7 over the experimental period. During the course of the experiment the proportion of tsetse infected with trypanosomes varied between 22.4 and 24.4 percent , of which 46 to 68 percent harboured metacyclic forms. Trypanosoma vivax was the the most common species found (in 61.2 percent of infected tsetse), followed by T. congolense (in 14.9 percent ) and T. brucei (in 1.8 percent ). Eight months after treatment the cumulative Trypanosoma infection rates in the cattle were 27.7, 58.5 and 77.4 percent in the group with the SRD implant, the group receiving the im injection, and the control group, respectively. Statistical analysis showed that the incidence of trypanosomiasis was significantly lower (P=0.006) in the group which received ISMM via the SRD than in the one which was treated with ISMM im.